FORECASTING THE NUMBER OF DEATH DUE TO TRAFFIC ACCIDENTS IN MEDAN CITY USING EXPONENTIAL SMOOTHING METHOD - Suhadi, Muhammad; Susiana, Susiana (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
This study aims to determine the prediction of the number of deaths due to traffic accidents in the city of Medan in 2009 - 2018. This study was conducted with quantitative forecasting, namely forecasting based on quantitative data in the past. The data of this study is data on the number of deaths due to traffic accidents in the city of Medan in 2009 - 2018 with a total of 10 years. Data were analyzed using Microsoft Excel with Exponential Smoothing method. The number of deaths due to traffic accidents in Medan City in 2019 was 244 people, in 2020 it was 219 people, and in 2021 it was 197 people with a MAPE of 0.1536659 or 15.36% with an alpha constant (α = 0.1). This shows that the level of accuracy at MAPE <20, meaning that the forecasting ability is good using the Exponential Smoothing method while the MAD value is 41.02 and the MSE value is 2677.54